2019
DOI: 10.1016/j.lfs.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cardio-metabolic risk factors is differentially elevated in obesity-prone Osborne-Mendel and obesity-resistant S5B/Pl rats

Abstract: Aims: Individual susceptibility to develop obesity may impact the development of cardiometabolic risk factors that lead to obesity-related comorbid conditions. Obesity-prone Osborne-Mendel (OM) rats expressed higher levels of visceral adipose inflammation than obesity-resistant, S5B/PI (S5B) rats. However, the consumption of a high fat diet (HFD) differentially affected OM and S5B rats and induced an increase in visceral adipose inflammation in S5B rats. The current study examined the effects of HFD consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Metabolic risk factors (inflammation, angiogenesis, oxidative stress) were more prevalent in the obese rats, compared to OR rats. Whereas cardiovascular key biomarkers were elevated in the obesity condition, these data suggested that an increased susceptibility to develop obesity is linked to an increased risk for cardio-metabolic disease ( 38 , 39 ). In this context, the OR group presented lower insulin value and larger area under the glycemic curve.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Metabolic risk factors (inflammation, angiogenesis, oxidative stress) were more prevalent in the obese rats, compared to OR rats. Whereas cardiovascular key biomarkers were elevated in the obesity condition, these data suggested that an increased susceptibility to develop obesity is linked to an increased risk for cardio-metabolic disease ( 38 , 39 ). In this context, the OR group presented lower insulin value and larger area under the glycemic curve.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, aerobic ET attenuates the tumor growth factor (TGF)-β positive stimulation and downstream effectors of fibrosis in the rat heart ( 37 ). Poret et al ( 38 ), evaluating cardio-metabolic risk factors in obesity-prone, Osborne-Mendel, and obesity-resistant S5B rats, showed that the LV weight and wall thickness were decreased in S5B rats with consumption of HFD. Furthermore, the authors observed that brain natriuretic peptide (BNP) and connective tissue growth factor (CTGF) mRNA expressions in LV were lower in S5B rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailing of the composition of the diets is essential to control the conditions of development of obesity and OR [ 3 , 20 ]. The fat profile found in HFD is a relevant variable, as it directly affects body fat gain and the development of metabolic disorders [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to Obesity (OR) is a growing research topic in the scientific community with a considerable increase in the number of publications in recent years [ 1 3 ]. However, the etiology of OR is still unknown in the literature, since its characterization was described more than three decades ago.…”
Section: Introductionmentioning
confidence: 99%